A comparison between modern research methods and Al-Mubarrad's brief approach (Journal of the College of Basic Education, 2023)
For more than a century, scholars have tried to return to heritage and draw from it and move its reservoirs to benefit from these reservoirs to serve humanity without discrimination. A long time has passed since attempts were made to study grammatical and linguistic sciences, and since the beginning of the twentieth century, serious attempts to study human heritage took their place in the avenue of human civilization to present treasures The different sciences folded by the hands of time and tried to bury them in the different waves of invasion in every part of the Arab world, so the need for serious and objective research arose in all subjects of science, especially the grammatical and linguistic lessons, and progress in that depends on the method and the method. The process of scientific research was set back only because of the lack of normalization of scientific methodologies: the tools of those methodologies fail to measure the phenomena that require delving into them, and people do not differ from their scientist or their ordinary person when they follow ways to acquire knowledge except that the first follows a specific program that leads to revealing the truth with the help of a group Rules dominate the course of the mind and define its operations until it reaches a known result, and the second works randomly and vaguely to form the net. There are inaccurate sentences that may make mistakes and may be correct. The research included an introduction with a brief summary of the life of Al-Mubarrad with three topics and a conclusion.